Manajemen Nyeri Kepala Dengan Kompres Hangat Pada Penderita Hipertensi Di Puskesmas Polokarto - SRIBEKTI, DINA; , Supratman, Ph. D (2016)
Hypertension is a risk factor for the third biggest cause of early death. World Health Organization (WHO) and The International Society of Hipertension stated there are currently 600 million people with hypertension world wide. Headache at the nape of the neck area of a major complaint in patient with hypertension. Stiffness in the nape of the neck caused by increased pressure on the walls of blood vessels in the neck that lead to blood flow is not smooth, and the end result of metabolism in the neck area due to lack of O2 and nutrients accumulate is inflammation in the area of attachment of muscles and bones that appeared pain. Pain that appears to disrupt daily activities. Acts of non pharmacologic can be given one of them with a warm compress is one of pain management by providing heat energy by conduction, where the heat is capable of causing vasodilation (widening of blood vessels), improve muscle relaxation to improve circulation and increase the incorporation of oxygen and nutrients to the tissues, the main purpose of nursing care for clients with pain is to relieve pain (scale 0-1), blood pressure within normal limits, capable to practices back pain management with warm compresses. The method used is descriptive method with case study approach, with a sample of Ny. WJ in Puskesmas Polokarto with observation, interview and literature study. The conclusion of the case is a matter of nursing patients about safety and comfort disorders (pain) head resolved, so that the intervention is stopped. The next action plan that provides support and motivation to get enough rest, and advise the patient to practices warm compresses when pain appears.